Penerapan Arsitektur Perilaku Dalam Redesain Lembaga Rehabilitasi Di Makassar - Embong Bulan, Muhammad Erwin; Alfiah, Alfiah; Syuaib, Mayyadah (The Department of Architecture, Faculty of Science and Technology, Alauddin Islamic University of Makassar, 2023)
As imperfect living beings, humans sometimes do good deeds and sometimes do evil deeds based on the lust in their hearts and minds. Humans are not aware that they will grow old and are getting closer to death. After making mistakes, humans tend to have a sense of regret and want to improve themselves to be much better. The authorities and the community are needed as a comprehensive response effort by working together actively and continuously. In medical science, most classes of drug drugs are helpful for treatment, but they can also be misused if they are not by the dosage or standard of treatment that is circulating legally. The behavioral architecture approach as a method of designing rehabilitation designs becomes a vehicle for improving human behavior and requires good humanitarian support.